Analysis of the intrinsic signals, extrinsic signals and the expected quality of the organic tortilla to assess its purchasing intentions - Brenda Patricia Gallegos-Hernández; Héctor Hugo Pérez-Villarreal; Igor Barahona; Yesica Mayett-Moreno (Cogent Business & Management, 2018)
The purpose of the following research is to analyze the expectations and perceptions of the consumer through the measuring of the intrinsic and extrinsic signals, as well as the expected quality of the organic tortilla to evaluate its impact over the purchasing intention. The design of the research was non- experimental, the scope was descriptive, correlational, causal and cross-sectional. The sampling method was non-probabilistic by convenience using a personal survey applied to a sample of 386 consumers at Tlaxcala's Alternative Market in 2017. This research demonstrates the importance of the consumer while looking for alternatives to assess their purchase. The importance it shows among the organic sector is related to the information obtained, in order to design marketing strategies oriented toward the processed food market, being able to improve the signaling of the product and the perception of the consumer.
Keywords: 650